Association of Food Consumption Patterns and Physical Activity Towards the Nutritional Status Of Students at Nuraida Islamic Boarding School In Bogor - Ramadhani, Rahma Varizka; Anwar, Khoirul; Maskar, Dadi Hidayat (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Adolescence is a period of rapid growth and development that requires optimal nutritional needs and physical activity. Adolescent girls are more susceptible to nutritional problems due to increased nutrient needs and a tendency to restrict food consumption, especially in boarding school environments with structured living systems. This study aims to determine the relationship between food consumption patterns and physical activity with the nutritional status of female students at Nuraida Islamic Boarding School, Bogor City. This study used an observational analytical design with a cross-sectional approach. The study subjects were 73 high school female students selected using a purposive sampling technique. Data on food consumption patterns were collected through food weighing and food records for 2x24 hours, while physical activity was measured using the Physical Activity Questionnaire for Adolescents (PAQ-A). Data processing involved editing, coding, data entry, and data cleaning. Relationship analysis was performed using the Spearman Rank test. The results showed that the majority of female students had good nutritional status (67.1%). Food consumption patterns based on type and frequency were classified as adequate, as indicated by consumption of more than four food groups on the first day (65.8%) and the second day (79.5%), as well as sufficient meal frequency on the first day (28.4%) and the second day (73.0%). However, the adequacy of energy and macro and micronutrients was still largely below the required levels. Physical activity was mostly classified as light (86.3%). There was no significant relationship between meal type and frequency with nutritional status, while physical activity did not show a significant relationship with nutritional status.